You are here:

# Algebra/maths - exponential equation

Question
2^(x+4) - x^(x+2)=3?

m^n=121 ,m and n whole nos then (m-1)^n+1=?

2^x=3^y=6^-z then 1/x+1/y+1/z=?

[16^(x+1) +20(4^2x)]/[2^(x-3)][8^(x+2)]

------------------------------------------------------------------------------------
2^(x+4) - x^(x+2)=3?

First note that x must be small, for large numbers don't have powers very close together.
For the first one, note that 2^2 = 4, and 3 is 1 less.
So if we had 4-1, that would be 3.
To get 2^(x+4) = 4, we would need x as -2, so that would give 2^2.
To get x^(x+2) = 1, we would need x as -2, for -2^0 = 1.
Thus, x = -2 is the answer.

------------------------------------------------------------------------------------
m^n=121 ,m and n whole nos then (m-1)^n+1=?

If m^n = 121, then note that 121 = 11^2, so m = 11 and n = 2.
If we are trying to find(m-1)^n + 1, that would be 10^2 + 1 = 101.
If it is really suppose to be (m-1)^(n+1), that would be 10^3 = 1000.

Also note that m=-11 works, since -11^2 = 121.
If that were the case, then the result would be -11^2 + 1 or -11^3.
That would be -1,21 + 1 =-120 or -11^3 = -1,331.

------------------------------------------------------------------------------------
2^x=3^y=6^-z then 1/x+1/y+1/z=?

If 2^x = 3^y = 6^-z, then take the ln() of all terms.
That gives ln(2^x) = ln(3^y) = ln(6^z).
It is known that ln(x^y) = y*ln(x), so this can be rewritten as x*ln(2) = y*ln(3) = z*ln(6).
Since 6 = 2*3, this can be rewritten as x*ln(2) = y*ln(3) = z*[ln(2)+ln(3)].
So it is known that y = x * ln(2) / ln(3) and z = x * ln(2) / [ln(2) + ln(3)].
All we need is to choose x, then y and z are given.

There are no integer solutions since some power of 3 never exist as being equal unless
x=0, y=0, and z=0, for then we would have 1 = 1 = 1.  If that were the case, then
1/x + 1/y + 1/z = 1/0 + 1/0 + 1/0 = undefined + undefined + undefined = undefined.

Now if this problem were changed to one with integer solutions ...

Now if it was x^2 = y^3 = z^6, they would have integer solutions.
They would be x = a^3, y = a^2, and z = a, for that would give
(a^3)^2 = (a^2)^3 = a^6, which is a^6 = a^6 = a^6.

If a = 1, that gives 1, 1, and 1, with each term being 1.

If a = 2, that gives 8, 4, and 2, with each term being 64.
The answer would be 1/8 + 1/4 + 1/2 = 7/8.

If a = 3, that gives 27, 9, and 3, with each term being 729.
The answer would be 1/27 + 1/9 + 1/3 = 13/27.

If a = 4, that gives 64, 16, and 4, with each term being 4,096.
The answer would be 1/64 + 1/16 + 1/4 = 21/64.

If a = 5, that gives 125, 25, and 5, with each term being 15,625.
The answer would be 1/125 + 1/25 + 1/5 = 31/125.

If there is something that is written incorrectly, ask again.

------------------------------------------------------------------------------------
16^(x+1) +20(4^2x)]/[2^(x-3)][8^(x+2)]

Note that [16^(x+1) +20(4^2x)]/[2^(x-3)][8^(x+2)] should really be written as
[16^(x+1) + 20(4^{2x})]/{[2^(x-3)][8^(x+2)]}.

I added '{' and '}' around both terms after the '/' symbol or else would do the division and then multiply all that by that last term.  This is a fact that often occurs because on the PC, the problem needs to be on one line and the last term is really suppose to be in the denominator.

I also added '{' and '}' in the 4^2x.  Since powers have precedence over multiplication,
as written we would have 16x.

I also put a ' ' after that + on top, just to clarify the problem.
The answer would be no different, but I like to put spaces around addition/subtraction terms to designate that each term is calculated individually.

For [16^(x+1) + 20(4^2x)]/{[2^(x-3)][8^(x+2)]}, it all depends on the choice of x.

If x = 0, we have (16 + 1) / [(1/8)(64)] = 17 / 8 = 2.125.

If x = 1, we have (16^2 + 20*4^2)/[(1/4)(1)] = (256 + 320)*4 = 576*4 = 2,304.
If you recognize 576 as being 24^2 and 4 as being 2^2, then note the answer would be 48^2,
for that is what 2,304 is. { I said this because 2,304 is recognized as 48^2. }.

If x = 2, we have (16^3 + 20*4^4)/(2*8^4). = (4,096 + 5,120)/8,192 = 9,216/8,192.
Note that 9,216 = 96^2, and that 96=3*2^5, so 9,216 = (3*2^5)^2 = 3^2 * 2^10.
This makes 9,216/8,192 = 9/8.

If x = 3, we have (16^4 + 20*4^6)/(1*8^6) = (65,536 + 81,920)/262,144 = 147,456/262,144.
Note that the top and bottom can be reduced by dividing them both by 2, many times.
If is 147,456/262,144 = 75,728/131,072 = 37,864/65,536 = 18,932/32,768 = 9,466/16,384 =
4,733/8,192.  Now the denominator is 2^13, and the numerator is not divisible by 2,
so that would be the final answer is x = 3.

If x = -1, it would be really simple.  It would be [1 + 20/16]/[(1/16)8] = (9/4)/(1/2) = 9/2.

If there is more to the last problem, ask again ... after Thanksgiving.
Questioner's Rating
 Rating(1-10) Knowledgeability = 9 Clarity of Response = 9 Politeness = 10 Comment thanks for the fast reply still going through the answer

Algebra

Volunteer

#### Scott A Wilson

##### Expertise

Any algebraic question you've got. That includes question that are linear, quadratic, exponential, etc.

##### Experience

I have solved story problems, linear equations, parabolic equations. I have also solved some 3rd order equations and equations with multiple variables.

Publications
Documents at Boeing in assistance on the manufacturiing floor.

Education/Credentials
MS at math OSU in mathematics at OSU, 1986. BS at OSU in mathematical sciences (math, statistics, computer science), 1984.

Awards and Honors
Both my BS and MS degrees were given with honors.

Past/Present Clients
Students in a wide variety of areas since the 80's; over 1,000 of them have been in algebra.